COMMERCIALIZATION OF COPYRIGHT CONTENT THROUGH DIGITAL PLATFORMS IN INDONESIA - Safiranita Ramli, Tasya; M. Ramli, Ahmad; Permata, Rika Ratna; Budhijanto, Danrivanto (Progressive Law Review, 2019)
With the new advances in the Industrial Revolution 4.0 era, which were initiated by artificial intelligence coupled with genetic engineering and nanotechnology, changes will occur in a very fast period of time and result in an impact on the economic industry and also governance in the presence of new business that was born of innovators to create strategies through digital platforms. In Indonesia, digital innovation is not only in one area, but also in the fields of education, food, health, which is also used as a new law in government that supports the Industrial Revolution 4.0 era. These developments also affected the world industry. The birth of the term Industrial Revolution 4.0 was a continuation of the previous industrial revolution. The Industrial Revolution 4.0 is an amalgamation of an optimized manufacturing industry with the latest internet technology.